K. M. Sibbald & Howard Young (eds.), T. S. Eliot and Hispanic modernity 1924-1993. University of Colorado, Boulder, 1994; 106 pp. - Cosgrove, Ciaran (El Colegio de México, 1995)
Se reseñó el libro: T. S. Eliot and Hispanic modernity 1924-1993.